Pengaruh Citra Merek dan Inovasi Produk terhadap Minat Beli Ulang Produk Roma di Kabupaten Sidoarjo - Maheswari, Inezella; Pudjoprastyono, Hery (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the relationship between brand image and product innovation on repurchase interest in Roma products located in Sidoarjo. Roma products are the focus where further research will be carried out in terms of innovation and brand image. Likert scale in quantitative with sample (non probability). 100 Roma customers were studied with Smart Pls analysis. The results of this research indicate that the relationship between brand image, product innovation and repurchase intention has a significant and positive influence on each other in Sidoarjo Regency.